Estimating the Corporate Income Tax Gap : The RA-GAP Methodology - Ueda, Junji (Technical Notes and Manuals; Technical Notes and Manuals ;, 2018)
The IMF Fiscal Affairs Department's Revenue Administration Gap Analysis Program (RA-GAP) aims to provide a quantitative analysis of the tax gap between potential revenues and actual collections, and this technical note explains the concept of the tax gap for corporate income tax (CIT), and the methodology to estimate CIT gaps. It includes detailed steps to derive the potential CIT base and liability with careful consideration for the theoretical differences between the coverage of statistical macroeconomic data and the actual tax base of CIT, and then compare the estimated results with actual declarations and revenues. Although the estimated gaps following the approach will have margins of errors, it has the advantage of using available data without additional costs of collection and suits initial evaluations of overall CIT noncompliance in a country.